PERAN CHARACTER STRENGTH TERHADAP RESILIENSI AKADMEIK PADA MAHASISWA YANG BEKERJA - Luthfi Noor Aini; Davita Variani; Nia Kusuma Wardhani (Universitas Muhammadiyah Gresik, 2024)
Background: Students who study and work face many daily challenges such as time constraints, work and study pressures, and busy schedules that can cause stress and interfere with individual mental health. Resilience is a factor that plays an important role so that individuals can survive in overcoming problems and adapting to stressful situations. Objective: This study examines whether there is an influence of character strength on resilience in working students. Method: This type of research is quantitative with simple regression analysis that measures the magnitude of the influence between the dependent variable and the independent variable. Total respondents were 149 working students in Yogyakarta Province. Results: Character strength variables can be used as predictors of academic resilience variables. The R square value of 0.163 indicates that 16.3% of the Character strength variable can predict the level of academic resilience in the subject. Conclusion: There is a significant relationship between Character strength and resilience in working students. The relationship between the two variables is positive, which means that if the Character strength in students is positive, the resilience is high, otherwise if the student's Character strength is negative, the resilience is low.